Analisis Wacana Tekstual Kumpulan Cerpen Tentang Kita dan Laut Karya Yetti A.Ka - Zita Sekar Graciavita; Agung Nugroho; Syaiful Abid (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to describe the textual discourse in the short story collection About Us and the Sea by Yetti A.KA. The type of research conducted is qualitative. The data collection techniques used in this research are literature study technique, note-taking technique, and coding technique. The overall research results found six elements of lexical markers and 88 data from 10 title collection of short stories About Us and the Sea by Yetti A.KA, including: repetition (repetition) totals 28 data, synonymy (matching words) totals 30 data, antonymy (opposite words) totals 15 data, collocation (collocation) totals 3 data, hyponymy (top-bottom relationship) totals 8 data and equivalence (equivalence) totals 4 data. From the results of data analysis, it can be concluded that the discourse in the collection of short stories About Us and the Sea by Yetti A.KA is a cohesive discourse because it is formed by a solid sentence structure. The coherence and wholeness of the discourse can certainly form a coherent meaning relationship. This is supported by the use of connecting means that are interrelated and do not deviate from the main idea for each topic of the problem in each data.